Foreign Enterprises in the Siberian Economy - Sysoeva, Natalia (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2019)
The purpose of the article is to identify the spatial character of foreign investment in Siberia where a considerable part of Russian export goods is produced for the markets of Europe and the Asia-Pacific region. A microeconomic approach was used, and the types and activities of enterprises with foreign capital were analysed. The main features were presented: the predominance of offshore investments, officially identified as foreign investment in the basic industries; increase in the share of investment into the mining industry and increasing dependence on China when moving east; high level of individual’s investment in services with fast capital turnover and minimal capital costs which forms a specific survival environment in the border areas with Mongolia and China. Three patterns of foreign investment in the Siberia are identified - western, central and eastern. The western pattern is characterised by a diversity of donor countries and investment in processing industries, the central one is based on the offshore capital in energy and semi-product industries, and in the eastern pattern investment into mining and logging prevails. The last type of investment is not receptive to innovations and new technologies, conserves and deepens the resource specialisation of industry for Asian markets of raw materials.